Hepatic Encephalopathy-Associated Cerebral Vasculopathy in Acute-on-Chronic Liver Failure: Alterations on Endothelial Factor Release and Influence on Cerebrovascular Function - Caracuel, Laura; Sastre, Esther; Callejo, María; Rodrigues-Díez, Raquel; García-Redondo, Ana B.; Prieto, Isabel; Nieto, Carlos; Salaices, Mercedes; Aller, Ma Ángeles; Arias, Jaime; Blanco-Rivero, Javier (Frontiers in Physiology, 2020)
The acute-on-chronic liver failure (ACLF) is a syndrome characterized by acute decompensation, hepatic encephalopathy (HE) and high mortality. We aimed to determine the mechanisms implicated in the development of HE-associated cerebral vasculopathy in a microsurgical liver cholestasis (MHC) model of ACLF. MHC was induced by ligating and extracting the common bile duct and four bile ducts. Sham-operated (SO) and MHC rats were maintained for eight postoperative weeks Bradykinin-induced vasodilation was greater in middle cerebral arteries (MCA) from MHC rats. Both N-Nitro-L-arginine (L-NAME) and indomethacin diminished bradykinin-induced vasodilation largely in arteries from MHC rats. Nitrite and prostaglandin (PG) F1 releases were increased, whereas thromboxane (TX) B2 was not modified in arteries from MHC. Expressions of endothelial nitric oxide synthase (eNOS), inducible NOS (iNOS) and cyclooxygenase (COX) 2 were augmented, and neuronal NOS (nNOS), COX-1, PGI2 synthase (PGI2S) and TXA2S were unmodified. Phosphorylation was augmented for eNOS and unmodified for nNOS. Altogether, these endothelial alterations might collaborate to increase brain blood flow in HE.